Hot carrier spatio-temporal inhomogeneities in ultrafast nanophotonics - Schirato, Andrea; Crotti, Giulia; Proietti Zaccaria, Remo; Alabastri, Alessandro; Della Valle, Giuseppe (New journal of physics, 2022)
Light-induced hot carriers in nanostructures and their corresponding optical nonlinearity have been extensively examined during the last decades. However, nonlinear optical effects dictated by the spatio-temporal evolution of out-of-equilibrium electrons at the nanoscale represent a much more recent research focus. Here we theoretically discuss the role of spatial inhomogeneities that energetic electrons feature across individual nanoantennas in metasurface configuration upon illumination with femtosecond laser pulses. As exemplary cases, we consider two-dimensional geometries of gold meta-atoms having either a high aspect ratio or a tapered cross-section and model their ultrafast optical response. A comparison with numerical results obtained either neglecting or accounting for spatial effects indicates that deep sub-wavelength spatio-temporal transients of carriers may have a significant impact on the dynamics of the all-optically modulated signal, with major quantitative corrections up to predicted changes in sign. Our results present hot-electron local inhomogeneities as an emerging subject with potentially relevant applications in various ultrafast nanophotonic configurations.